Kom Wasit (Egitto): le terme ellenistiche e la successiva occupazione romana - Mondin, Cristina; Kenawi, Mohamed; La Rosa, Nunzia; Patanè, Maria Lucia (Rei Cretariae Romanae Fautorum Acta, 2022)
The archaeological site of Kom Wasit is located 30 km south of Rosetta and 50 km south-east of Alexandria. During the survey of the site as part of the 2008 season of the Beheira Survey, a Hellenistic tholos bath complex that had been previously excavated in the 1940s was relocated. A geophysical survey was conducted at Kom Wasit in 2014 and it revealed the remains of the structures of an entire town. This prompted the Italian archaeological project to excavate the entire area of the bath in 2016. The complex consisted of two circular tholoi equipped with 18 hip-bathtubs. Besides the tholoi, other structures were unearthed; in particular, three water basins were discovered connected by a small canal. The first one was built in the south-eastern masonry of the western tholos. Its fill contained dozens of 2nd – 1st centuries BC bowls, jugs, unguentaria, and common ware potteries. The area was ransacked after the abandonment of the bath complex, which was then re-used as a cemetery in the mid-Roman period. The findings include terracotta sarcophagi and amphorae, as well as human remains without sarcophagi. The investigations indicate that the exposed part of the cemetery was probably looted in the past; indeed, coins dated to the 5th and 6th centuries AD are attested at Kom Wasit.